The genus Selasia Laporte, 1838 (Coleoptera: Elateridae: Agrypninae) in Sri Lanka - Packova, Gabriela; Kundrata, Robin (Zootaxa, 2021)
The neotenic click-beetle genus Selasia Laporte, 1838 has a centre of diversity in the tropical Africa but also includes several species known from the Palearctic and Oriental regions. In this study, we review the Selasia fauna of Sri Lanka. We describe S. ivanae sp. nov., redescribe S. apicalis Pic, 1914, and discuss the systematic placement of S. isabellae Bourgeois, 1909, which is probably a firefly and is considered incertae sedis.